Acupuncture on treating asthma: A protocol for systematic review and meta analysis - Chen, Yan-Ming (Medicine (Baltimore), 2020)
BACKGROUND: Asthma is one of the most common chronic diseases in the world, with approximately 300 million asthma patients worldwide. The mortality rate of asthma is 1.6 to 36.7 / 100,000 people, and China has become one of the countries with the highest asthma death rate in the world. Asthma is a chronic allergic airway inflammatory disease. Patients with this disease may have symptoms such as cough, wheezing, and difficulty breathing. For many years, Western medicine has mainly used anti-inflammatory, anti-bronchial spasm, asthma, cough and oxygen to treat this disease, but the effect is not good. Clinical studies in recent years have found that the use of acupuncture in the treatment of bronchial asthma has a good clinical application prospect. This study was conducted to study the effect of using acupuncture to treat asthma. METHODS AND ANALYSIS: We will search for PubMed, Cochrane Library, AMED, EMbase, WorldSciNet; Nature, Science online and China Journal Full-text Database (CNKI), China Biomedical Literature CD-ROM Database (CBM), and related randomized controlled trials included in the China Resources Database. The time is limited from the construction of the library to November 2019. We will use the criteria provided by Cochrane 5.1.0 for quality assessment and risk assessment of the included studies, and use the Revman 5.3 and Stata13.0 software for meta-analysis of the effectiveness, recurrence rate, and symptom scores of asthma. ETHICS AND DISSEMINATION: This systematic review will evaluate the efficacy and safety of acupuncture for asthma. Because all of the data used in this systematic review and meta-analysis has been published, this review does not require ethical approval. Furthermore, all data will be analyzed anonymously during the review process Trial.